Targeting PIKfyve-driven lipid metabolism in pancreatic cancer - Caleb Cheng; Jing Hu; Rahul Mannan; Tongchen He; Rupam Bhattacharyya; Brian Magnuson; Jasmine P. Wisniewski; Sydney Peters; Saadia A. Karim; David J. MacLean; Hüseyin Karabürk; Li Zhang; et al. (Nature, 2025)
Abstract Pancreatic ductal adenocarcinoma (PDAC) subsists in a nutrient-deregulated microenvironment, making it particularly susceptible to treatments that interfere with cancer metabolism 1,2 . For example, PDAC uses, and is dependent on, high levels of autophagy and other lysosomal processes 3–5 . Although targeting these pathways has shown potential in preclinical studies, progress has been hampered by the difficulty in identifying and characterizing favourable targets for drug development 6 . Here, we characterize PIKfyve, a lipid kinase that is integral to lysosomal functioning 7 , as a targetable vulnerability in PDAC. Using a genetically engineered mouse model, we established that PIKfyve is essential to PDAC progression. Furthermore, through comprehensive metabolic analyses, we found that PIKfyve inhibition forces PDAC to upregulate a distinct transcriptional and metabolic program favouring de novo lipid synthesis. In PDAC, the KRAS–MAPK signalling pathway is a primary driver of de novo lipid synthesis. Accordingly, simultaneously targeting PIKfyve and KRAS–MAPK resulted in the elimination of the tumour burden in numerous preclinical human and mouse models. Taken together, these studies indicate that disrupting lipid metabolism through PIKfyve inhibition induces synthetic lethality in conjunction with KRAS–MAPK-directed therapies for PDAC.